Multiple sclerosis : the history of a disease - Murray, T. J. (Demos, 2005)
Multiple Sclerosis: The History of a Disease won a 2005 ForeWord Book of the Year Silver Medal! Click here to learn more about the ForeWord Book of the Year Awards. The basic facts about multiple sclerosis are well known: it is the most common neurologic disease of young adults, usually beginning with episodic attacks of neurologic symptoms, then entering a progressive phase some years later. Its onset has an average age of 30, and occurs in about 1 in 500 individuals of European ancestry living primarily in temperate climates. There appears to be a complex interaction between a genetic predis.